Vendeurs ambulants dans l’espace touristique à Gênes : politiques d’éviction, résistances et arrangements - Sébastien Jacquot; Cristina Notarangelo (L'Espace Politique)
Genoa tourist center (Porto Antico) whitnesses a constant presence of Senegalese street vendors, despite public policies of eviction. This paper analyses the reasons and dynamics for this remaining, leading to question the political dimension of tourism, through the regulation of tourist places, that define legitimate uses and users. First the eviction policies are addressed, which rely on tourism and urban planning, as well as on the continuous presence of various police and security forces. These policies reveal their logics, based on auto-exclusion, but also their contradictory and differentiated dimensions. Nevertheless, the streetvendors manage to resist and remain in these spaces, through informal accommodations and arrangements, but also through mobilisations, supported by anti-racist activists. Hence the regulation of tourist spaces can be red as a crucible for dynamics of politicization.